Investigation of interactions in the mechanically activated a-Fe2O3/Li2CO3 reagents by thermal analysis; Journal of Thermal Analysis and Calorimetry; Vol. 148 - Nikolaev E. V. Evgeny Vladimirovich; Lysenko E. N. Elena Nikolaevna; Surzhikov A. P. Anatoly Petrovich; Elkin V. D. Vladimir Denisovich (2023, 2023)
Title screen